1979
DOI: 10.1063/1.437252
|View full text |Cite
|
Sign up to set email alerts
|

Electronic three wave mixing spectra of transient species produced by UV laser photolysis of benzene

Abstract: Intense three wave mixing (3WM) spectra are reported for transient fragments produced by 266 nm laser photolysis of benzene and several substituted benzenes. Single pulse broadband 3WM spectra taken with an optical multichannel analyzer establish that the fragments are primary photoproducts obtained under collision-free condition. The spectra consist of many features at anti-Stokes frequency shifts of 900–3100 cm−1 from a 532 nm ω1 pump. 90° fluorescence studies of the photolysis zone show that C2 is produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…the diatomic species C 2 [147][148][149], CH [150], and NO [151,152]. Furthermore polyatomic molecules such as NO 2 [153], NH 2 [154], and C 2 H 2 [155] have been investigated using this technique.…”
Section: Electronic Enhancement Of Cars Allows Detection Of Minor Spementioning
confidence: 99%
“…the diatomic species C 2 [147][148][149], CH [150], and NO [151,152]. Furthermore polyatomic molecules such as NO 2 [153], NH 2 [154], and C 2 H 2 [155] have been investigated using this technique.…”
Section: Electronic Enhancement Of Cars Allows Detection Of Minor Spementioning
confidence: 99%
“…In fact, we have observed that the broad feature at 4685/~, related to Swan's band transitions from the a3II~ vibrationally excited states above ~ 4000cm -1, increased more than all the other peaks measured in the range (4580 + 6100)/~. The later features were tentatively assigned by Gross et al [7] to resonance-enhanced CARS from highly excited vibrational levels of the AllIu C~ state lying about 15000cm -1 above the ground state. Present results show that colinear CARS is a simple technique for contemporary on-line detection of C6H6 and of its C2 fragments in laser-induced dissociation processes.…”
Section: -Experimentalmentioning
confidence: 60%
“…Most of the fragment peaks shown in fig. 2b) and listed in table II have also been observed at lower pressures and photolysis laser powers by [7] in the UV photodissociation of C6 H6 at 266 nm. These features are there discussed as probably related to resonantly enhanced CARS signals coupling different electronic states of the C2 photofragment.…”
Section: -Experimentalmentioning
confidence: 70%
See 2 more Smart Citations